2016
DOI: 10.1038/srep39153
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of the Complete Mitochondrial Genome of Leucoma salicis (Lepidoptera: Lymantriidae) and Comparison with Other Lepidopteran Insects

Abstract: The complete mitochondrial genome (mitogenome) of Leucoma salicis (Lepidoptera: Lymantriidae) was sequenced and annotated. It is a circular molecule of 15,334 bp, containing the 37 genes usually present in insect mitogenomes. All protein-coding genes (PCGs) are initiated by ATN codons, other than cox1, which is initiated by CGA. Three of the 13 PCGs had an incomplete termination codon, T or TA, while the others terminated with TAA. The relative synonymous codon usage of the 13 protein-coding genes (PCGs) was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 48 publications
10
31
0
Order By: Relevance
“…Recent studies showed that cGAS has remarkable anti-viral properties against different positive-strand RNA viruses, including the Flavivirus family members. However, not negative-strand RNA viruses [85,86], suggesting that common characteristic features observed during the life cycle of positive strand RNA virus, including the massive rearrangement of internal membranes, may stimulate a mislocalization of DNA that could act as a substrate to induce the cGAS/STING signaling pathway [86]. For example, cGAS−/− mice displayed enhanced rates of infection and mortality when compared with wild type mice, which was infected with the +ssRNA West Nile virus.…”
Section: Mitochondrial Dna and Anti-viral Immune Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies showed that cGAS has remarkable anti-viral properties against different positive-strand RNA viruses, including the Flavivirus family members. However, not negative-strand RNA viruses [85,86], suggesting that common characteristic features observed during the life cycle of positive strand RNA virus, including the massive rearrangement of internal membranes, may stimulate a mislocalization of DNA that could act as a substrate to induce the cGAS/STING signaling pathway [86]. For example, cGAS−/− mice displayed enhanced rates of infection and mortality when compared with wild type mice, which was infected with the +ssRNA West Nile virus.…”
Section: Mitochondrial Dna and Anti-viral Immune Responsesmentioning
confidence: 99%
“…For example, cGAS−/− mice displayed enhanced rates of infection and mortality when compared with wild type mice, which was infected with the +ssRNA West Nile virus. This infectious agent probably triggers the release of mitochondrial DNA into the cytosol, which is then recognized by the nucleic acid sensors in the cytoplasm, subsequently induce the immune system to clear the infection [86].…”
Section: Mitochondrial Dna and Anti-viral Immune Responsesmentioning
confidence: 99%
“…To amplify the D. stuposa mitogenome, the universal (F1-R13) and specific primers (S1F-S3R) were used to perform PCR amplification (Table 1) (Sun et al, 2016). All PCR amplifications were executed using high fidelity DNA Polymerase (PrimeSTAR® GXL, Takara, Dalian, China).…”
Section: Pcr Amplification and Fragment Sequencingmentioning
confidence: 99%
“…All PCR amplifications were executed using high fidelity DNA Polymerase (PrimeSTAR® GXL, Takara, Dalian, China). PCRs was performed according to Sun et al (2016) with extension times depending on the putative length of target fragment. PCR product size was determined by PeerJ reviewing PDF | (2019:07:39693:3:0:NEW 7 Feb 2020)…”
Section: Pcr Amplification and Fragment Sequencingmentioning
confidence: 99%
“…Altogether, the two fragments represented approximately 60% of the complete mitogenomes, amounting to 10 of the 13 known mt PCGs and 12 of the 22 tRNAs (Fig. 2), and displayed a conserved gene arrangement relative to other lepidopteran mitogenomes (Cameron & Whiting, 2008;Sun et al, 2016;Djoumad et al, 2017).…”
Section: Mitochondrial Genome Sequencing and Annotationmentioning
confidence: 99%